The results of surgical treatment of preschool and primary school age children with congenital deformation of the spine in isolated hemivertebra: Comparative analysis - Nurbek Nadirov; Sergey Vissarionov; Alexandra Filippova; Dmitriy Kokushin; Vitaliy Sazonov (Frontiers Media S.A., 2022)
IntroductionDespite a detailed study of the natural development of congenital spinal deformity in an isolated hemivertebra and the methods of surgical correction of this pathology, some issues remain unresolved. The age at which the surgical correction of congenital spinal deformity should be performed is a controversial issue among specialists dealing with this problem. The aim of the work was to conduct a comparative analysis of the results of spinal deformity correction in children with congenital kyphoscoliosis with an isolated hemivertebra of preschool and primary school age.Materials and methodsThe study involved 26 patients aged from 1 year 9 months to 9 years 6 months (10 girls and 16 boys) with congenital kyphoscoliosis caused by an isolated hemivertebra. The patients underwent surgical interventions of partial or complete resection of the hemivertebra with adjacent intervertebral discs from the dorsal or combined approach, correction, and stabilization of congenital deformity of the spine with a posterior multi-support metal structure. All the patients were divided into two groups by age: the first group-children under 4 years old (14 children), and the second group-children of 6 years and older (12 children).ResultsMetal fixation during surgical treatment in children of primary school and preschool ages was carried out in the majority of cases in a polysegmental manner. Regarding the approach for surgical treatment, it can be noted that in the 2nd group of patients, preference was more often given to the dorsal surgical approach. The duration of the surgical intervention and the amount of blood loss between different age groups did not have statistically significant differences. In the group of children of preschool age, in three cases, the destabilization of the metal structure was noted in the early postoperative period when control radiographs were performed after surgical treatment. In the group of older children, after surgical treatment, the spinal dysplastic deformity above or below the zone of metal fixation was detected in three cases.ConclusionThe effectiveness of surgical treatment of congenital deformity was significantly higher in children of the younger age group compared to school-age patients.